Assessing the in-plane seismic performance of rammed earth walls by using horizontal loading tests. (15th August 2017) - El-Nabouch, Ranime; Bui, Quoc-Bao; Plé, Olivier; Perrotin, Pascal
Highlights: Experimental studies with horizontal loading tests. Four walls with two height/length ratios were built and tested. Application of the pushover method to assess the seismic performance of rammed earth structures. The seismic performance was evaluated following Eurocode 8, in different conditions (seismicity zones and soil types). Abstract: Rammed earth (RE) construction is attracting renewed interest throughout the world thanks to its sustainable characteristics: very low embodied energy, advantageous living comfort due to substantial thermal inertia, good natural moisture buffering and an attractive appearance. This is why several studies have recently been conducted to investigate RE. However, there have not yet been sufficient studies on the seismic performance of RE buildings. This paper presents an experimental study on the static nonlinear pushover method and its application to the seismic performance of RE structures. Several walls with different height/length ratios were built and tested to obtain nonlinear shear force–displacement curves. By transposing these shear force-displacement curves to an acceleration–displacement system and using the standard spectra presented in Eurocode 8, the performance points were determined, making it possible to assess the seismic performance of the walls studied in different conditions (seismicity zones and soil types).